2010
DOI: 10.1007/s10490-010-9226-4
|View full text |Cite
|
Sign up to set email alerts
|

Effects of governance on investment decisions and perceptions of reporting credibility: Investment experience of Taiwanese individual investors

Abstract: This paper examines the effects of governance strength on individual investors' investment decisions and their perceptions of the credibility of financial reporting by Taiwanese companies. It also examines whether the investment experience of individual investors influences their perceptions and decisions. Our experimental results show that governance strength enhances the price that individual investors are willing to pay for stocks, along with the perceived credibility of firm reporting. Furthermore, the ass… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
24
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(32 citation statements)
references
References 37 publications
8
24
0
Order By: Relevance
“…Corporate governance mechanisms, commonly the assignment of independent directors, was considered by our participants (F8; F10; F13; R15), which is consistent with Chang and Wei (2011). However, our participants viewed management credibility and integrity as more important than the presence of independent directors.…”
Section: Impressions Of Integrated Reportingsupporting
confidence: 70%
See 1 more Smart Citation
“…Corporate governance mechanisms, commonly the assignment of independent directors, was considered by our participants (F8; F10; F13; R15), which is consistent with Chang and Wei (2011). However, our participants viewed management credibility and integrity as more important than the presence of independent directors.…”
Section: Impressions Of Integrated Reportingsupporting
confidence: 70%
“…However, Holm and Rikhardsson (2008) and Cohen et al (2011) found retail investors prioritised economic information related to corporate investment plans, market share and customer satisfaction above ethical guidelines and environmental programs. With specific reference to Taiwan, Chang and Wei (2011) suggested that retail investors value corporate governance mechanisms such as the presence of independent directors.…”
Section: Investors' Use Of Non-financial Disclosuresmentioning
confidence: 99%
“…This paper's contribution for practice is that it suggests that family business researchers, practitioners, and policymakers take family ownership into consideration when investigating dividend payout policy of family firms in a Confucian-influenced country since controlling family ownership may positively or negatively relate to dividend payout at different levels of family ownership concentration. Similar to Chang and Wei (2011), we argue that individual investors should incorporate corporate dividend policy to make their investment decision on the securities of family firms in Taiwan.…”
Section: Contributionsmentioning
confidence: 80%
“…Specifically, they employ an innovative experimental technique to identify whether Taiwanese investors will pay more for stocks of companies that are ostensibly better governed than their rivals. Chang and Wei (2011) show that governance strength can enhance the price that individual investors are willing to pay for stocks. However, the association between governance strength and the willingness to pay more for a stock is moderated by the investment experience of individuals.…”
Section: Conclusion and Future Researchmentioning
confidence: 99%